Pembatasan Akses Menggunakan MAC Address dengan Metode Access Control List - Muhammad Aditya Rabbani Adit; Martanto Martanto; Yudhistira Arie Wijaya (JISKA (Jurnal Informatika Sunan Kalijaga), 2022)
The Cangehgar Cyber Command Center of the 14th Arhanud/ PWY Battalion from Cirebon City is one of the offices with IT equipment to assist the job. The servers, like the office PCs, are connected via the local network. Due to the risk of leaking secret data from within, network security concerns must be handled so that unauthorized users cannot mistakenly access the server. It seeks to limit access when there are administrative customers and employees in each room by utilizing the access control list approach using a MAC address. Access to the server is restricted to the administrator's computer, while access to the employee's PC is disallowed. Then the questionnaire was distributed to find out the respondent's assessment of the access control list. According to the results of the study on security indicators, access control lists containing MAC addresses are useful in limiting access to server computers.